Collaborative Governance pada Revitalisasi Sungai Sekanak di Kota Palembang - Afrijal Afrijal; Muhammad Quranul Kariem (Jurnal Pemerintahan dan Politik, 2021)
This study describes the practice of collaborative governance on the revitalization of the Sekanak River in the city of Palembang, where it will be analyzed using the theoretical approach of Ansell and Gash related to the criteria of collaborative governance. The Regional Head directly leads the implementation of the revitalization of the Sekanak River, which is a very interesting phenomenon to be studied in depth from the collaborative governance perspective. Community involvement is very important in realizing the goal of revitalizing the Sekanak River, because the community will play a role in preserving, maintaining, and utilizing the potential of the Sekanak River. This research is a qualitative research using the literature study method in collecting secondary materials and for conducting analysis. The result of this study is that the local government does not implement collaborative governance in the revitalization of the Sekanak River in the city of Palembang, this happens because of the very technocratic approach used by the government in the Sekanak River revitalization policy. The recommendation from this research is that local governments should open the widest possible space for community participation, especially on issues that directly intersect with the community.Â Keywords: Â revitalization, government, collaborative